Adulteration and quality assessment of tomato paste: a study of the Lebanese market - Fatima Habib; Salma Khazaal; Elie Bou Yazbeck; Elie Bou Yazbeck; Espérance Debs; Suhair Sunoqrot; Nicolas Louka; Nada El Darra (Frontiers in Nutrition)
Food adulteration has emerged as a significant global issue, impacting consumer health and fair-trade practices. This study aimed to evaluate the quality and potential adulteration with starch in tomato paste products available in the Lebanese market. A total of 41 local and imported tomato paste samples, without starch declarations, were collected from the Lebanese market and analyzed for starch usage and various quality parameters (total soluble solids, Bostwick consistency, viscosity, titratable acidity, color, and dry matter content), as well as compliance with Libnor and Codex Alimentarius standards. Results revealed that 37% of samples failed to meet starch usage standards, and 27% did not comply with the required total soluble solids (>24%), while all samples complied with acidity standards (<7%). Compliant samples had significantly higher values for total soluble solids, acidity, dry matter, and color compared to non-compliant ones (p < 0.01). A comparison of local and imported tomato paste products showed no significant differences in physicochemical properties, color, shelf life, or price, with parameters being similar across samples. Among local samples, 48% did not comply with the starch usage standard, and 26% failed to meet the required total soluble solids level. In contrast, imported samples adhered to starch usage standards, although 30% did not comply with TSS levels. This study highlights the prevalence of adulteration in local and imported tomato paste products in Lebanon and calls for further enforcement measures to ensure consumer protection and fair trade.